Preparation of Stearic Acid/Graphene oxide Based Form-Stable Composite Phase Change Materials - OKTAY, BURCU (My University, 2018)
Composite phase change materials (PCM) of stearic acid/graphene oxide were prepared by thiol-alkyne click coupling reaction.Stearic acid was firstly modified with propargyl to introduce thiol-yneclickable sites. Different amounts of graphene oxide were added to thiol-alkyne clickable formulation. To evaluate phase change properties of PCMs differential scanning calorimeter (DSC) was used. Thermal stability and degradation profiles of PCMs were investigated. The structural characterization of stearic propargyl ester and PCMs was performed by aTR-FTIR spectroscopy. The addition of graphene oxide increased the maximum weigh loss temperature from 328 to 351 ˚C with respect to the base formulation. Moreover, the crosslinking of stearic acid prevented the leakage of PCMs.

Stearik asit-grafen oksit kompozit faz değişim malzemeleri (PCM) tiyol-alkin klik kapanma reaksiyonu ile hazırlandı. Öncelikle stearik asit tiyol-yne klik gruplarının bağlanması amacıyla modifiye edildi. Farklı miktarlarda grafen oksit tiyol-klik formülasyonuna eklendi. PCM’lerin faz değişim özelliklerini incelemek için diferansiyel taramalı kalorimetre (DSC) kullanıldı. PCM’lerin termal kararlılık ve bozunma profil incelendi. Stearik propargyl esteri ve PCM’lerin yapısal karakterizasyonu ATR-FTIR spektroskopisi ile gerçekleştirildi. Grafen oksit eklenmesiyle baz formülasyona göre maksimum kütle kaybı sıcaklığı 328 dan 351 ˚C ye yükseldi. Aynı zamanda stearik propargyl çapraz bağlanmasıyla PCM’lerin akma problem engellendi.
Stearik Asit/Grafen oksit Esaslı Form-Kararlı Kompozit Faz Değişim Malzemelerinin Hazırlanması
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler